The Paradox of Piety and Violation of Marriage Norms in the Si Doel The Movie - Nuzul Iskandar; Pyrma Aranika; Afridawati Afridawati (Islamic Studies Journal for Social Transformation, 2021)
This article intends to provide an explanation of the paradox of piety and violations of marital legal norms shown in Si Doel The Movie, as well as a juridical analysis of these violations. This study uses a cross-disciplinary approach, namely the semiotic approach and juridical-empirical analysis. The data was collected qualitatively with documentation techniques, then the semiotic analysis of the Roland Barthes model was carried out, then the marriage law analysis was carried out. This study reveals that marital life in the movie is filled with signs that can be interpreted as images of piety and obedience which in Indonesian society develop as a myth of household resilience, but these images are not positively correlated with marital life and adherence to marital norms. , such as norms regarding marriage registration, polygamy procedures, rights and obligations of husband and wife, and parental responsibilities towards children. In fact, this film does not provide a good marriage law education for Muslims in Indonesia. However, this article is limited to looking at the implementation and violations of marital norms in the context of individual behavior. Further research is needed on aspects of legal culture in order to get a more complete picture.